TO THE ISSUE OF A DIFFERENTIATED, BIOPATHOGENETIC APPROACH TO THE SELECTION OF INTERVENTION FOR VARIOUS CLINICAL AND ANATOMICAL FORMS OF SEVERE TRAUMATIC BRAIN INJURY (World Science, 2023)
The work, based on many years of experience and in-depth analysis of significant clinical material - 3500 surgical interventions for various clinical and anatomical forms of severe traumatic brain injury (TBI), carried out in 1515 cases in the pre-computer period and in 1990 - in the post-computer period, shows the evolution views on neurotrauma and the advantage of a differentiated approach to the choice of intervention, taking into account the biomechanism and neuropathomorphological features of various clinical and anatomical forms of TBI; shows how they have changed, with the introduction of adequate diagnostic tools and neuroimaging (CT and MRI) approaches to the choice of interventions depending on and taking into account the biomechanism and pathomorphological basis of various clinical and anatomical forms of severe traumatic brain injury. With the introduction of computer diagnostics, the possibilities of various methods of intervention were revised: if possible, preference was given to osteoplastic trephination, which, in case of swelling and prolapse of the brain - in case of gross violations of the craniocerebral volume-capacitive relationships, in the computer period, the intervention ended with decompressive craniotomy with subcutaneous preservation bone flap – in 1096 cases out of 1990 interventions. In the remaining 894 cases, the intervention was completed using the osteoplastic method. In 217 of them, it was carried out in an improved, modified form: a wide bone flap, with moderate cerebral edema, was not removed. On top of the plastically extended hard shell, it was guided to the sawing site, as if in the form of an “apron,” and loosely fixed with periosteal sutures. When the edema subsided, the bone flap was placed in place, and if necessary, it was easily connected with ligatures passed through microholes along the edge of the craniotomy and in symmetrical places of the sawed bone flap and brought out. In case of inertial injuries, with multihemispheric-multifocal brain damage and with a volumetric hemorrhagic component, in 939 cases one was performed - and in 157 observations - two-sided optimally extended decompressive craniotomy, among which in 49 cases bilateral hemicranectomy was successful. After 1096 decompressive interventions, 554 (41.4%) of the victims died; in the remaining 894 cases, a wide traditional and modified craniotomy with loose fixation of the bone flap was also performed, involving the parabasal sections of the anterior and middle cranial fossa; in 84 cases - bifrontal craniotomy with falxotomy, in 593 - extended traditional osteoplastic trepanation, and in 217 cases - also extended, but modified osteoplastic craniotomy. Death was noted in 27 (32.1%), 110 (18.5%) and 11 (5.1%) cases, respectively. The overall mortality rate in this group - among 894 cases with osteoplastic craniotomy - was 16.6%. Postoperative mortality among all 1990 interventions for various clinical and anatomical forms of TBI in the post-computer period amounted to a total of 30.3%. Thus, taking into account the biomechanism and pathomorphological basis of TBI, a differentiated, biopathogenetic approach to the choice of intervention, it was possible to reduce, from year to year, postoperative mortality from 36-38% in the pre-computer period, to 29-30% in the computer period, at 35-45 % according to various neurosurgical clinics.